TRANSFORMATION OF EX-HTI PROPAGANDA BEFORE AND DURING COVID-19 PANDEMIC - Ghazali, Ali Al (UI Scholars Hub, 2021)
Since it’s dissolution in 2017, HTI ex-members transformed into multiple communities and utilizing internet to conduct propaganda, recruitment, and coordination. Covid-19 pandemic created new opportunity for spread of radicalism because of economic recession and increased poverty. HTI ex-members continue the struggle through underbouw organizations like GEMA Pembebasan, BacktoMuslimIdentity Community (BMI), and MuslimahNewsId. Rise in internet usage during pandemic helps expose people to HTI khilafah propaganda. Uploaded contents are provocative and targeting mainly millennials and women. This increased the potential of sectarian conflict and proliferation of radical islamist movement in the coming years. Government could tackle this by providing Islamic education in college, conducting contra-narration in social media, accelerating economic recovery, and strengthening the implementation of Pancasila.